Psychometric Properties of the Sexually Aggressive Behaviors Scale: Factor Structure, Reliability, and Construct Validity in a Sample of Portuguese Female College Students - Rosa, Pedro J. (International journal of offender therapy and comparative criminology, 2024)
This study investigates the psychometric properties of the Sexually Aggressive Behaviors Scale (SABS) in a sample of 1,632 heterosexual Portuguese female college students, aged between 18 and 39 years old (M = 22.40; SD = 4.31). The internal structure of the scale was investigated, along with analyses of the internal consistency, and validity evidence in relation to external variables. Participants completed an online survey that was disseminated using Portuguese universities’ mailing lists and social networks. Results supported a single factor solution consisting of 10 items. Evidence was gathered in favor of the internal consistency and convergent/discriminant validity in relation to other variables, such as rape myths, psychopathic traits, and perception of intimacy. This study adds to the evidence of the SABS being an appropriate evaluation tool with female college students, allowing the rigorous assessment of sexual violence as committed by community women against a reluctant male partner.